2006
DOI: 10.1177/009155210603300302
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Web Accessibility Knowledge and Needs at Oregon Community Colleges

Abstract: A needs assessment determined Oregon community college staff knowledge of (a) accessible information technology (IT) guidelines, (b) IT-related disability laws, (c) legal obligations regarding Web accessibility, and (d) perceived level of current Web accessibility. Training needs were assessed and training suggestions were solicited. IT staff demonstrated higher levels of Web accessibility guidelines knowledge, and disability/student services staff best understood disability laws. At most schools, knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Second, similar to the findings of Wisdom et al (2006), HBCU leadership should consider providing professional development for their faculty and staff focused on web accessibility. As previously stated, many of the web accessibility errors in this study are relatively simple to fix.…”
Section: Discussion and Implications For Research And Practicementioning
confidence: 74%
See 3 more Smart Citations
“…Second, similar to the findings of Wisdom et al (2006), HBCU leadership should consider providing professional development for their faculty and staff focused on web accessibility. As previously stated, many of the web accessibility errors in this study are relatively simple to fix.…”
Section: Discussion and Implications For Research And Practicementioning
confidence: 74%
“…Their study found information technology (IT) professionals and disability/student services staff members were the most knowledgeable about disability laws—including web accessibility standards—yet IT professionals and disability staff members rarely collaborated to ensure web accessibility across campus. This finding led Wisdom et al (2006) to encourage communication between IT and disability/student services departments to collaboratively publish web-accessible websites and provide professional development for those unfamiliar with web accessibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the Internet and other web-based technology can provide time unlimited access; however, for some, access barriers are created because of its use. Many students with disabilities face challenges when using computers and accessing electronic formats, including the Internet (Erickson et al, 2009;Stoneham, 2005;Wisdom et al, 2006). Erickson et al (2009) investigated the use of the Internet to deliver information and services to community college students with and without disabilities.…”
Section: Accessibility and Utility Of Technologymentioning
confidence: 99%